A future vision for disease control in shrimp aquaculture. Issue 2 (7th February 2019) - Flegel, Timothy W.
Abstract : Aquaculture is the fastest‐growing animal production sector, and shrimp production already exceeds that of the capture fishery. Viruses and bacteria account for the majority of disease losses for shrimp farmers. Viral pandemics in the mid 1990s and, more recently, a bacterial pandemic from 2009 to 2015 have led to the conclusion that future, sustainable shrimp aquaculture will depend on the development of more efficient, biosecure production facilities that cultivate specific pathogen‐free (SPF) shrimp, genetically improved for growth and disease tolerance or resistance. Major requirements for development, maintenance, and use of SPF stocks in aquaculture are effective pathogen surveillance and disease prevention methods. When protective measures fail and diseases occur in production ponds, there are currently only a few approved and practical therapeutic methods available for use with bacterial pathogens and none so far for viral pathogens. To improve existing methods of prevention and therapy and to develop new ones, research is being carried out on the nature of shrimp–pathogen interactions. Promising results have been obtained at the laboratory level for possible applications involving the use of immunostimulants for "immune priming" or "trained immunity" of RNA interference and of endogenous viral elements. Some of these promising new directions are discussed.